2006
DOI: 10.1143/jjap.45.l233
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Crystal Orientation of Ru Under-Layer on Initial Growth of Copper Chemical Vapor Deposition

Abstract: The effect of Ru crystal orientation on the deposition behavior of chemical vapor deposition (CVD) Cu was investigated. The crystal orientation of Ru films was modulated by adjusting sputtering temperature. Ru(001) and random orientation films were obtained by sputtering at 300 C and room temperature, respectively. CVD Cu on Ru with the (001) crystal orientation had a smooth morphology and a strong (111) peak. However, CVD Cu on the Ru film with the random orientation had a rough surface and a random orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…Redistribution subject to ECS terms of use (see 128.255.6.125 Downloaded on 2015-06-12 to IP By XRD we found that the ALD copper grown onto Ru(001)/hydrogen using either Cu-DI-1 at 150°C or Cu-KI-2 at 160°C gave fully oriented Cu(111) films, as shown in Figure 11 below for Cu-DI-1. Similar results have been reported for CVD copper deposited onto Ru(001) (11). The lattice mismatch between Cu(111) and Ru(001) is only 4% which probably accounts for the excellent adhesion observed for the Cu/Ru(001) laminates described above which all passed the Scotch tape test, typically pulling adhesive from the tape.…”
Section: Ald Coppersupporting
confidence: 81%
“…Redistribution subject to ECS terms of use (see 128.255.6.125 Downloaded on 2015-06-12 to IP By XRD we found that the ALD copper grown onto Ru(001)/hydrogen using either Cu-DI-1 at 150°C or Cu-KI-2 at 160°C gave fully oriented Cu(111) films, as shown in Figure 11 below for Cu-DI-1. Similar results have been reported for CVD copper deposited onto Ru(001) (11). The lattice mismatch between Cu(111) and Ru(001) is only 4% which probably accounts for the excellent adhesion observed for the Cu/Ru(001) laminates described above which all passed the Scotch tape test, typically pulling adhesive from the tape.…”
Section: Ald Coppersupporting
confidence: 81%
“…7 In particular, plasma-enhanced atomic layer deposition ͑PEALD͒ can deposit high density films at low processing temperatures, which is critical for the growth of thin continuous Cu films that are resistant to agglomeration. 8,9 The agglomeration of chemically deposited thin Cu layers is a major roadblock to extending Cu seed layer technology. 10 However, while a number of groups have reported the growth of Cu films by ALD, the suitability of such processes for seed layer applications has not been established.…”
mentioning
confidence: 99%
“…20 nm Ru and Ta, which is deposited by sputtering method on TaN diffusion barrier, are used as substrate of Cu CVD. The sputtering temperature of Ru is 300 o C, which result in strong (001) orientation (20).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, to deposit Cu seed layer having a good Cu adhesion and morphology, a barrier material must have no reactivity with fluorine and a good Cu wettability. In this point of view, Ru is the best candidate of a new barrier material due to its good Cu wettability and the property of noble metal (11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%